ADHD and accidents over the life span – A systematic review. (June 2021) - Brunkhorst-Kanaan, Nathalie; Libutzki, Berit; Reif, Andreas; Larsson, Henrik; McNeill, Rhiannon V.; Kittel-Schneider, Sarah
Highlights: ADHD patients are at increased risk of accidents and injuries, however risk changes over the life span. Types of accidents and injuries in ADHD differ over the life span. ADHD medication seems to decrease the risk of accidents and injuries in all ages. ADHD with mental disorder comorbidities appears to show further augmented accident and injury risk. Abstract: Studies have demonstrated an increased risk of accidents and injuries in children, adolescents and adults with attention-deficit/hyperactivity disorder (ADHD). However, little is known about how accident risk may alter over the lifespan. Additionally, it would be important to know if the most common types of accidents and injuries differ in ADHD patients over different age groups. Furthermore, there is increasing evidence of an ameliorating effect of ADHD medication on accident risk. Lastly, the underlying risk factors and causal mechanisms behind increased accident risk remain unclear. We therefore conducted a systematic review focusing on the above described research questions. Our results suggested that accident/injury type and overall risk changes in ADHD patients over the lifespan. ADHD medication appeared to be similarly effective at reducing accident risk in all age groups. However, studies with direct comparisons of accident/injuries and effects of medication at different age groups or in old age are still missing. Finally, comorbidities associated with ADHD such as substance abuse appear to further increase the accident/injury risk.